Assessing the impact of ecological forest restoration on soil carbon stocks in Sub-Saharan Africa: a systematic review - Vuyo Qasha; Alen Manyevere; Trevan Flynn; Chuene Victor Mashamaite (Carbon Management)
Land use changes, especially deforestation and agricultural expansion, have had significant impacts on the global climate crisis through greenhouse gas (GHG) emissions. This has led to adverse effects on climate systems, biodiversity, forestry product supply, and soil quality. Global efforts such as the sustainable development goals, specifically Sustainable Development Goal(SDG) 13 (Climate Action) and SDG 15 (Life on Land), aim to mitigate land degradation and biodiversity loss. However, the challenge of land degradation presents a significant barrier to achieving these goals. This systematic review investigates the effectiveness of ecological forest restoration initiatives in bolstering soil Carbon (C) stocks within Sub-Saharan Africa (SSA) forested areas. The review elucidates the impact of restoration efforts on soil C dynamics by synthesizing findings from 22 relevant studies conducted across various regions of SSA forested areas. The studies encompass diverse restoration strategies, including agroforestry systems, forest and landscape restoration, and selective logging assessments. Key findings highlight the positive influence of ecological restoration on soil C stocks, particularly in enhancing ecosystem resilience and promoting sustainable land use practices. Moreover, the review identifies critical research gaps and methodological considerations for future studies. Limitations in the literature, such as language bias and geographic coverage, underscore the need for more comprehensive and multilingual approaches to research. This review contributes significant insights into the effectiveness of ecological forest restoration in mitigating deforestation threats, promoting sustainable land management, and safeguarding vital ecosystem services in SSA forested areas.